ANALYSIS OF THE EFFECTIVENESS OF BUDGET EXPENDITURE CONTROL SYSTEMS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Budget expenditure control systems are essential in ensuring the proper allocation, disbursement, and monitoring of public funds. Their effectiveness directly impacts a country’s fiscal discipline, transparency, and economic stability. This paper aims to analyze the effectiveness of such systems by examining the key control mechanisms, the challenges faced by governments in implementing these systems, and the best practices adopted globally. Additionally, the article explores the influence of digital transformation on improving budget control systems.